Prognostic value of the geriatric nutritional index in colorectal cancer patients undergoing surgical intervention: A systematic review and meta-analysis - Mao, Yiqing; Lan, Jiarong (Frontiers in Oncology, 2022)
Background: We reviewed the literature to assess the prognostic ability of the geriatric nutritional risk index (GNRI) for patients with colorectal cancer (CRC) undergoing curative surgery. Methods: The online databases of PubMed, CENTRAL, ScienceDirect, Embase, and Google Scholar were searched for articles reporting the relationship between GNRI and outcomes in CRC patients. English language studies were searched up to 28th April 2022. Results: Ten studies with 3802 patients were included. Meta-analysis indicated that patients with low GNRI had significantly poor overall survival (HR: 2.41 95% CI: 1.72, 3.41 I2=68%) and disease-free survival (HR: 1.92 95% CI: 1.47, 2.49 I2=49%) as compared to those with high GNRI. The meta-analysis also indicated a significantly higher risk of complications with low GNRI as compared to high GNRI (HR: 1.98 95% CI: 1.40, 2.82 I2=0%). The results did not change on subgroup analysis based on study location, age group, GNRI cut-off, and sample size. Conclusion: Current evidence indicates that GNRI can be a valuable prognostic indicator for CRC patients undergoing surgical intervention. Patients with low GNRI have poor overall and disease-free survival and a higher incidence of complications. Clinicians could use this simple indicator to stratify patients and formulate personalized treatment plans.